Computed Tomography (CT) of blunt abdominal trauma: the frequency of incidental findings, how it was documented in radiology report and the implication of these findings to acute trauma care - Hassan, Radhiana; Che Mohamed, Siti Kamariah; Kamarulzaman, Mohd Nazli; Abdul Aziz, Azian (Malaysian Medical Associations, 2014)
The wide use of computed tomography (CT) scanning for patients with blunt abdominal trauma can reveal incidental findings that vary in their importance. We evaluated these findings, how it was reported by radiologists and its implication on the trauma care. In 30 out of 154 patients, 32 incidental findings were discovered (19.5%). Out of these 32 findings, only 3 cases (9.4%) were considered significant and required immediate attention from the managing team. In all these 3 cases, the findings were described in the body of the report and highlighted in the conclusion section at the end of the radiology report. However, similar reporting style was used in only 58.4% of cases with moderate clinical concern and 23.5% of cases with little clinical concern. In 41.2% of cases with little concern, the incidental findings were not mentioned in the radiology report. In conclusion, incidental findings in CT scan performed for blunt abdominal trauma were common but many were clinically insignificant. There is little consistency in radiology reporting of these findings especially those with moderate and little clinical concern.